Co-movements between Latin American and U.S. stock markets: convergence after the financial crisis (2013)
Currently, the world is facing a continuous process of integration in different aspects and financial markets are no exception to this development. Despite the fact that global integration is gradual, one can find some specific events that might help to accelerate this trend. This paper shows that after the financial crisis of 2008, which mainly occurred in the United States, the Latin American stock markets exhibit a higher level of convergence, measured by the correlation between the annual returns of their stock market indices. Additionally, we find convergence in the coefficient of sensitivity between Latin American and U.S. stock markets, using dynamic linear models at the regional level. In particular, we uncover consistent movements in the levels of sensitivity between the daily annual returns of the Latin American indices and the S&P index after the financial crisis. This kind of convergence might be a positive sign to accelerate the integration process in Latin America stock markets, which has had a slow development since its beginning a few years ago.